Uang Panai And Its Legality: When Tradition Intersects With Civil Law - Rizky Wisudawan Katjong; Revie Kurnia Katjong (Leges Privatae, 2025)
This study examines the legal position of uang panai, a traditional form of payment in Bugis-Makassar marriage customs, within Indonesia’s civil law system. The practice, deeply rooted in local culture, symbolizes respect, social status, and familial honor. However, its contemporary implementation often intersects with the formal legal order, raising questions regarding its classification as a lawful civil contract, a conditional gift, or an adat-based moral obligation. Using a normative juridical approach, this article analyzes relevant provisions of the Indonesian Civil Code (KUHPerdata), the 1945 Constitution, and Law No. 48 of 2009 on Judicial Power, alongside empirical findings from legal and sociological studies. The results show that while uang panai fulfills the elements of a binding agreement under Article 1320 of the Civil Code, its absence of written documentation and inconsistent enforcement create legal uncertainty. The state’s constitutional recognition of customary law under Article 18B(2) of the Constitution remains largely declarative rather than substantive. Consequently, disputes involving uang panai are often settled through informal adat forums without enforceable legal authority. To harmonize tradition and modern law, this research recommends the formulation of local regulations (peraturan daerah) and the development of judicial precedents that establish fair, proportional, and gender-sensitive standards for customary contracts. Such legal integration would ensure that uang panai remains a respected cultural practice while achieving the legal certainty and justice mandated by Indonesia’s civil law framework.